2019
DOI: 10.1063/1.5115364
|View full text |Cite
|
Sign up to set email alerts
|

Building energy efficiency policies and practices in Pakistan: A literature review

Abstract: The household sector in Pakistan became the largest consumer of electricity which is responsible for more than 51% of the national consumption. The Building Energy Code of Pakistan was developed in 1990, yet the institutional setup regarding energy efficiency & conservation is inadequate. There is lack of experts and implementation of policies at national and provincial level. The study aims to explore the energy efficiency and conservation policies in Pakistan and their impact on reducing household energy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…These codes not only allow energy savings but also helps to maintain good environmental quality and sustainability. Note that the awareness level of people in IPB is very poor towards building codes [139,140], a good understanding is required at all levels to gain advantage and build energy efficient living environment.…”
Section: Buildings Energy Efficiency Codes (Beecs)mentioning
confidence: 99%
“…These codes not only allow energy savings but also helps to maintain good environmental quality and sustainability. Note that the awareness level of people in IPB is very poor towards building codes [139,140], a good understanding is required at all levels to gain advantage and build energy efficient living environment.…”
Section: Buildings Energy Efficiency Codes (Beecs)mentioning
confidence: 99%
“…The cement plaster is then applied to both the inner and outer surfaces for the wall finishing. These houses are mainly constructed without any thermal insulation in walls, roofs, and floors [53][54][55]. Table 4 presents five different materials used for external wall construction type (X 2 ) to perform sensitivity analysis.…”
Section: Determination Of Design Variablesmentioning
confidence: 99%
“…These temperatures are mainly for the buildings with HVAC systems. We used this data as there is no such standard for the residential buildings in Pakistan [53,66]. There is a need to identify the suitable indoor temperatures for the buildings in different climatic zones of Pakistan.…”
Section: Main Findings and Recommendationsmentioning
confidence: 99%
“…The Pakistan Green Building Council (PGBC) establishment is also a constructive step towards improved energy efficiency in the building sector [5]. Mahar et al reviewed the energy efficiency policies in Pakistan and concluded that there is a lack of implementation and practice of energy efficiency policies [22]. Pakistan's poor energy policies have plunged the country into a severe economic crisis since 2006 [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Mahar et al reviewed the energy efficiency policies in Pakistan and concluded that there is a lack of implementation and practice of energy efficiency policies [22]. Pakistan's poor energy policies have plunged the country into a severe economic crisis since 2006 [22,23]. The 2006 financial crisis started with a shortage of electrical energy and its insufficient production to meet the increased demand [8,23], which later changed to problems in the transmission and distribution of electrical energy [24].…”
Section: Introductionmentioning
confidence: 99%